Marketing plans how to prepare them, how to profit from them - McDonald, Malcolm; Wilson, Hugh 1962- (Wiley, 2016)
In this text, the process of marketing planning - from initial assessment of a company's business plan to the steps necessary to ensure a company achieves its profit targets - is fully explained.
Revised edition of the authors' Marketing plans, 2011. - Includes bibliographical references and index. - Print version record
Keywords: Marketing -- Management; Marketing -- Planning; Marketing; Gestion; Marketing; Planification; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Marketing; Management; Marketing; Planning